## Formula of a plus b whole cube (a plus b whole cube formula)

Exam Tricks : This Free PDF Notes Contains a+b whole cube formula For Upcoming Sarkari Exams. In addition, You can easily download SSC, UPSC, IBPS Bank PDF on A plus b ka whole cube ka formula from this website. However, a plus b whole cube (a+b)³=a³+3a²b+3ab²+b³ is very important to crack any SSC, UPSC, IAS, Railway, RRB NTPC exams in India.

Formula of a plus b whole cube (a plus b whole cube formula) : Dear Examtrix.com (Exam Tricks) followers, That is to say, this important PDF Book is about a+b whole cube formula. Similarly, at this platform we share a plus b ka whole cube Handwritten notes pdf in Hindi-English and a+b cube formula Free Pdf Study material for Sarkari exam Jobs. Above all, जो SSC, UPSC Books Notes का नाम a+b the whole cube है.

Today, we are sharing a+b whole cube formula, SSC CGL free notes online, freeupscmaterial. We Share (a+b) whole cube Study Material according to SSC, UPSC Syllabus. On the other hand, This Free PDF Notes (Formula of a plus b whole cube (a plus b whole cube formula) and a minus b cube or a minus b whole cube is important for various Sarkari exams like UPSC, IAS, RAS, UPPSC, MPPSC, BPSC, SSC CGL, CHSL, CPO, what is a+b whole cube Notes For State PSC, CTET, Sub inspector, Patwari exam, Revenue office Exams all over India.

#### A+B whole cube formula Topics

• ( a − b ) 3 = a 3 − b 3 − 3 a b ( a − b )
• ( a − b ) 3 = a 3 − b 3 − 3 a b ( a − b )
• ⟹ ( a − b ) 3 = a 3 − b 3 − 3 a 2 b + 3 a b 2.
• ⟹ ( a − b ) 3 = a 3 − b 3 − 3 a b ( a − b )
• (a + b)2 = a2 + 2ab + b2
• (a – b)2 = a2 – 2ab + b2
• (a + b) (a – b) = a2 – b2
• (x + a) (x + b) = x2 + (a + b) x + ab
• (x + a) (x – b) = x2 + (a – b) x – ab
• (x – a) (x + b) = x2 + (b – a) x – ab
• (x – a) (x – b) = x2 – (a + b) x + ab
• (a + b)3 = a3 + b3 + 3ab (a + b)
• (a – b)3 = a3 – b3 – 3ab (a – b)
• (a + b)4 = a4 + 4a3b + 6a2b2 + 4ab3 + b4
• (a – b)4 = a4 – 4a3b + 6a2b2 – 4ab3 + b4
• (x + y + z)2 = x2 + y2 + z2 + 2xy +2yz + 2xz
• (x + y – z)2 = x2 + y2 + z2 + 2xy – 2yz – 2xz
• (x – y + z)2 = x2 + y2 + z2 – 2xy – 2yz + 2xz
• (x – y – z)2 = x2 + y2 + z2 – 2xy + 2yz – 2xz
• x3 + y3 + z3 – 3xyz = (x + y + z) (x2 + y2 + z2 – xy – yz -xz)
• x+ y2 = 1212 [(x + y)2 + (x – y)2]
• (x + a) (x + b) (x + c) = x+ (a + b + c)x2 + (ab + bc + ca)x + abc
• x3 + y3 = (x + y) (x– xy + y2)
• x3 – y3 = (x – y) (x+ xy + y2)
• x2 + y2 + z2 – xy – yz – zx = 1212 [(x – y)2 + (y – z)2 + (z – x)2]